Erdheim–Chester disease: expanding the spectrum of cutaneous manifestations. (8th September 2019) - Kobic, A.; Shah, K.K.; Schmitt, A.R.; Goyal, G.; Go, R.S.; Guo, R.; Rech, K.L.; Sartori‐Valinotti, J.C.; ,
Summary: Background: Erdheim–Chester disease (ECD) is a rare condition and there is limited information available regarding its cutaneous manifestations. Objectives: To describe the clinical and histopathological features of cutaneous involvement in ECD. Methods: This study is a single‐centre retrospective analysis of patients 18 years old and older with biopsy‐proven diagnosis of ECD between 1 January 1990 and 1 April 2017. Patients from this cohort were screened for cutaneous manifestations, and BRAF c.1799T>A (p.V600E) mutational analysis was conducted in novel skin manifestations. Primary outcomes included cutaneous manifestations (morphology and topography of lesions) and BRAF mutation status in novel cutaneous findings. Results: Of 71 patients with ECD, 15 patients (21%; median age 52 years) presented with cutaneous manifestations. The most common finding was the presence of xanthelasma‐like lesions ( n = 8). Two patients had nonfacial cutaneous xanthomas. Seven patients presented with nonxanthomatous cutaneous involvement, with the most common finding being subcutaneous nodules ( n = 5). A single patient presented with granuloma annulare‐like lesions. Another patient with mixed ECD and Langerhans cell histiocytosis presented with lightly scaling, pink‐red macules. In three patients, the appearance of skin lesions was the first manifestation of the disease. Most patients presented with bone/extremity pain, weight loss and other constitutional symptoms at the time of diagnosis. The BRAF V600E mutation was not found in patients with panniculitis‐like and granuloma annulare‐like lesions. Conclusions: The most common presentation in ECD is the presence of periorbital xanthelasma‐like lesions. Other presentations include nonfacial cutaneous xanthomas, panniculitis‐like lesions and granuloma annulare‐like lesions. Associated symptoms at presentation include bone/extremity pain and weight loss. What's already known about this topic? Erdheim–Chester disease is a rare form of non‐Langerhans cell histiocytosis characterized by lipid‐laden macrophage infiltration of tissue and subsequent fibrosis. Cutaneous involvement is found in approximately 25% of patients, with the majority presenting with periorbital xanthelasma‐like lesions. What does this study add? We report two novel cutaneous findings: panniculitis‐like lesions and granuloma annulare‐like lesions. Associated bone/extremity pain and weight loss should raise suspicion for Erdheim–Chester disease. Abstract : Linked Comment:  Rose. Br J Dermatol 2020; 182 :273–274 .